A mountain of information - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The Website, for the Year of the Mountain (2002) is online and expanding fast. Available in French, English and Spanish it has sections on the world s mountain ranges, upcoming events, publications, news and key themes including gender, water, soil...